Pemberdayaan Zakat Untuk Usaha Produktif Sebagai Penopang Perekonomian Masyarakat Palangka Raya masa Pandemi - Rahmad Kurniawan; Jefry Tarantang; Noorhana Sesar Sari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article aims to understand the scope of zakat regarding its role as a source of state wealth. The writing of the paper is carried out using a literature study method sourced from library books, research journals, laws, and relevant article websites. Zakat as a source of state wealth is a method of managing assets belonging to Muslims which will be used for the benefit of the people in order to build a just and prosperous country's economy. Zakat is one of the instruments in macroeconomics that allows the economy to continue running at a minimum level. Zakat is property that must be issued by a Muslim or business entity to be given to those who are entitled to receive it in accordance with Islamic law. Basically zakat is shown to eliminate the gap between the rich and the poor, because the wealth in the world is solely a deposit from God to humans to be managed properly. For this reason, the potential of zakat as a support for the economy in Indonesia is one of the efforts to manage assets as well as possible by prioritizing the benefit of the people.